Colouring mechanism and firing process of celadon from the Xiangzhou kiln in Anyang, China, from the 5th-7th century. Issue 8 (July 2023) - Li, Jihong; Wang, Shuangshuang; Liu, Xiaomin; Fang, Keke; Wu, Bo; Zhao, Wenjun; Feng, Xiangqian; Feng, Songlin; Zhao, Dan; Li, Bo; Li, Pengcheng; Zhao, Weijuan; et al.
Abstract: The Xiangzhou kiln was the largest celadon kiln site in northern China from the Northern and Southern Dynasties to the Sui Dynasty (5th-7th centuries). In order to investigate the colouring mechanisms and firing process of two types of celadon (yellow-green and earthen-yellow glazes) from the Xiangzhou kiln, samples were tested and analysed using OM, ED-XRF, TD, SEM-EDS, LRS, XPS and UV-Vis-NIR. The study results show that most of the samples in the two enamels have different formulations. The celadon glaze of the Xiangzhou kiln contains a small amount of quartz, anorthite and other crystals. The yellow-green glaze is fired in a reducing atmosphere and the earthy yellow glaze is fired in an oxidising atmosphere. The colouring mechanism of the Xiangzhou kiln celadon is mainly dominated by the chemical colouring of ionic colouring and aided by structural colouring caused by the microstructure (bubbles, various crystals, fractal structures, etc.).